Towards Canine Rabies Elimination in South‐Eastern Tanzania: Assessment of Health Economic Data. Issue 3 (24th February 2016) - Hatch, B.; Anderson, A.; Sambo, M.; Maziku, M.; Mchau, G.; Mbunda, E.; Mtema, Z.; Rupprecht, C. E.; Shwiff, S. A.; Nel, L.
Summary: An estimated 59 000 people die annually from rabies, keeping this zoonosis on the forefront of neglected diseases, especially in the developing world. Most deaths occur after being bitten by a rabid dog. Those exposed to a suspect rabid animal should receive appropriate post‐exposure prophylaxis (PEP) or risk death. However, vaccination of dogs to control and eliminate canine rabies at the source has been implemented in many places around the world. Here, we analysed the vaccination and cost data for one such campaign in the area surrounding and including Dar es Salaam, Tanzania and estimated the cost per dog vaccinated. We also estimated the cost of human PEP. We found that the cost per dog vaccinated ranged from 2.50 to 22.49 across districts and phases, with the phase average ranging from 7.30 to 11.27. These figures were influenced by over purchase of vaccine in the early phases of the programme and the significant costs associated with purchasing equipment for a programme starting from scratch. The cost per human PEP course administered was approximately 24.41, with the average patient receiving 2.5 of the recommended four vaccine doses per suspect bite. This study provides valuable financial insights into programme managers and policymakers working towards rabies elimination.